QVida+: Quality of life continuos estimation for clinical decision support - Reis, Luis Paulo (2019)
Advances in the last decades in the areas of medical science and patients treatment resulted in a decrease in the mortality rate but also an increase in the number of patients with chronic diseases. This increased life expectancy of patients with chronic diseases often involves great suffering and considerable adverse effects for the patients. Thus, in addition to prolonging life, it is essential to increase the quality of life (QoL) of patients. QoL is now considered an important aspect in clinical practice for patients with chronic illnesses, but the methods to assess, in an automatic or semi-automatic manner, QoL, and their use in clinical decision support are still underexplored and their applications are virtually inexistent. The QVida + solution is based on scientific and technological developments in the areas of quality of life and mobile devices, with the goal of creating a new paradigm for the evaluation and use of QoL in clinical practice. The solution devised is based on an adaptive information system (IS) able to use physical and behavioral data of the patient, gathered by sensors and mobile devices, in conjunction with machine learning techniques, allowing continuous assessment of QoL based on measurement tools that significantly reduce the questionnaires response time without affecting the patients daily life. Continuous assessment of QoL and its rapid use on a clinical decision support system will enable a better quality and more supported decision, patient-centered, by the physician, allowing for an increased quality of life of patients.